2011
DOI: 10.1111/j.1365-2966.2010.18002.x
|View full text |Cite
|
Sign up to set email alerts
|

Thin accretion discs around millisecond X-ray pulsars

Abstract: Millisecond X-ray pulsars have weak magnetic dipole moments of ∼10 16 T m 3 compared to ordinary X-ray pulsars with dipole moments of 10 20 T m 3 . For this reason a surrounding accretion disc can extend closer to the millisecond X-ray pulsars, and thus reach a higher temperature, at which the opacity is dominated by electron scattering and radiation pressure is strong. We compute the self-similar structure of such a geometrically thin axisymmetric accretion disc with an internal dynamo. Such models produce si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Here, as was studied by Tessema & Torkelsson (2011), we integrate Equation (39) for the inner region inwards from very small radius ∼ 12.5 and Λ = 1/3π. The dimensionless parameters γ, γ dyn and α ss are 1, 10 and 10 −2 , respectively.…”
Section: Global Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, as was studied by Tessema & Torkelsson (2011), we integrate Equation (39) for the inner region inwards from very small radius ∼ 12.5 and Λ = 1/3π. The dimensionless parameters γ, γ dyn and α ss are 1, 10 and 10 −2 , respectively.…”
Section: Global Solutionsmentioning
confidence: 99%
“…This figure depicts the variations of Λ as a function of r for all ǫ = 0.45, 0.15 and 0. All solutions are case V inner boundaries except −0.15 and −0.45 (Tessema & Torkelsson 2011).…”
Section: Global Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They introduced a new solution for an accretion disc around a magnetic star. [11], hereafter Paper II, have also studied the thin accretion disc around millisecond X-ray pulsars, which is the extension of Paper I. In both Papers they have developed a model for steady-state disc and found that the torque generated by the internal dynamo is stronger than the torque generated due to the shear.…”
Section: Introductionmentioning
confidence: 99%